Phenological and pomological properties of autochthonous apple cultivars in North Montenegro - Božović Đina; Jaćimović Vučeta; Lazović Biljana; Adakalić Mirjana (Agroznanje, 2015)
Autochthonous apple cultivars have been adapted to the existing agro-ecological conditions for over a long period time in northern Montenegro, and have great economic importance. The aim of this work was to study their phenological and pomological properties on the most interesting recommend for further cultivation on a large scale in this area. The research on 14 autochthonous apple cultivars was conducted in situ in the period 2008-2009. The earliest ripening (the beginning of August) was determined on Petrovaca, and the latest (the beginning of November) on Zukvaca cultivar. The fruit weight varied from 37,5 of Petrovaca to 187 g of Busuta. Poor coloured cultivars are dominated. The fruit of Busuta and Pazarka cultivars with a significant amount of soluble solids, 15.2% or 14.7%, can be good raw material for industrial processing. Based on twoyear average data for 11 properties, UPGMA dendogram analysis was performed, which showed a high degree of variability among the studied cultivars dividing them 3 groups and 1 independent accession.